Heater lamp product design as hypothermia prevention using qfd (quality function deployment) - Subhan, Subhan; Anshar, Khairul; Muarif, Agam; Ningtiyas, Dinda; Pandey, Govinda Prashad; Isa, Muzamir (Journal of Renewable Energy, Electrical, and Computer Engineering, 2022)
Every year the number of climbers increase, there are at least 70,000 climbers including researchers. The increase in the number of climbers will certainly increase the mortality risk of hypothermia. At least 18 people died from hypothermia in 2014 to 2015. The risk of hypothermia can be reduced by handling such as providing warmth to the patient. Warmth can be created by using a tool that produces the right heat, easy and safe to use, easy to carry and also affordable. This is the basis for researches to conduct research on designing heating products in tents as an effort to prevent hypothermia. This research uses the QFD (Quality Function Deployment) method in processing the results of the consumer’s voice, design the product concept, screening and selecting concept and analysis the final product design. Based on the data collection and processing that has been carried out, there are 10 criteria for consumer needs and interests for product, including practical tools to carry, safe to use, can warm the body to have additional functions as cellphone chargers. While the alternative concept chosen in the form of cylindrical tube, using a Li-ion battery, and a frame made of polypropilene plastic. From the chosen concept, then a heating lamp model is designed in the display when used and stored.